Pearson and yates statistics for professional performance according to job quality - Cortez Gutiérrez, Hernán Óscar; Cortez Gutiérrez, Milton Milcíades; Durand Gonzales, César Ángel; Espinoza Flores, Braulio Pedro; Guevara Llacza, César Miguel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of our research is to determine the impact of demand for work and psychological resources on professional performance. The quality of work was evaluated according to validated instruments and its normality was established. We have that psychological resources and job demand impact professional performance with a multiple Pearson correlation of 0.91. Pearson’s correlation between job quality and professional performance was 0.69 and p value was 0.004. Spearman’s correlation between psychological resources and professional performance was 0.735 and p value of 0.002.